The Role of Good Corporate Governance in Moderating the Impact of Capital and Credit on Firm Value: Evidence from Indonesian Banks - Zaldin, Asri; Khomsiyah (Santoso Academy Network, 2026)
This study investigates the effect of credit and capital on firm value, with corporate governance (CG) disclosure as a moderating variable, in banking companies listed on the Indonesia Stock Exchange (IDX). Using secondary data from Banks’ published financial statements over the period 2016–2021, this research applies Moderated Regression Analysis (MRA) to test the proposed hypotheses. The results show that capital has a positive and significant effect on firm value, while the loan-to-deposit ratio (LDR) does not significantly influence firm value. Furthermore, CG disclosure strengthens the relationship between capital and firm value, indicating that governance transparency enhances the signaling effect of capital to the market. However, CG disclosure does not moderate the relationship between LDR and firm value. This study is subject to certain limitations. Although the inclusion of 2022 financial statements was initially planned, incomplete reporting restricted the sample to banks with available data for the 2016–2021 period. In addition, the analysis is limited to banking firms listed on the IDX. CG disclosure data were obtained through content analysis in accordance with regulations issued by the Indonesian Financial Services Authority (OJK). Despite these limitations, the findings contribute to the literature on banking governance and firm value in emerging markets.